2019
DOI: 10.1021/acs.jmedchem.9b01196
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Late-Stage Optimization: Profiling Thermodynamics by Preorganization and Salt Bridge Shielding

Abstract: Structural fixation of a ligand in its bioactive conformation may, due to entropic reasons, improve affinity. We present a congeneric series of thrombin ligands with a variety of functional groups triggering preorganization prior to binding. Fixation in solution and complex formation have been characterized by crystallography, isothermal titration calorimetry (ITC), and molecular dynamics (MD) simulations. First, we show why these preorganizing modifications do not affect the overall binding mode and how key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 74 publications
0
22
0
1
Order By: Relevance
“…Diminishing the solvent exposure of this salt bridge potentially has an influence on its stability. For instance, it has been earlier demonstrated that shielding a salt bridge between ligand and protein from the solvent contributes to the binding 46 . This stabilized salt bridge interaction between Glu71 and Lys53 contributes to the enhanced conformational stability of the αC-helix.…”
Section: Discussionmentioning
confidence: 99%
“…Diminishing the solvent exposure of this salt bridge potentially has an influence on its stability. For instance, it has been earlier demonstrated that shielding a salt bridge between ligand and protein from the solvent contributes to the binding 46 . This stabilized salt bridge interaction between Glu71 and Lys53 contributes to the enhanced conformational stability of the αC-helix.…”
Section: Discussionmentioning
confidence: 99%
“…In probing the structure activity relationship (SAR) of adenosine derivatives as A 3 AR agonists, we discovered that introduction of a (N)-methanocarba (bicyclo[3.1.0]­hexyl) ring system in place of ribose leads to favorable affinity and selectivity. , This rigid ribose substitution pre-establishes a ligand conformation that is highly compatible with the A 3 AR binding requirements, possibly due to entropic reasons. , As demonstrated in both the ribose and methanocarba series, other modifications that are conducive to high A 3 AR affinity are 5′-alkylamide and C2-ethynyl groups, as in 3 – 5 . A 5′-methyl- or 5′-ethyl-amide group also tends to increase A 3 AR agonist efficacy in functional assays. A C2-(5-chlorothien-2-ylethynyl) substitution was associated with a long duration and efficacy in chronic pain tests.…”
mentioning
confidence: 99%
“…12,13 This rigid ribose substitution pre-establishes a ligand conformation that is highly compatible with the A 3 AR binding requirements, possibly due to entropic reasons. 16,17 As demonstrated in both the ribose and methanocarba series, other modifications that are conducive to high A 3 AR affinity are 5′-alkylamide and C2-ethynyl groups, as in 3−5. 18−21 A 5′methyl-or 5′-ethyl-amide group also tends to increase A 3 AR agonist efficacy in functional assays.…”
mentioning
confidence: 99%
“…1. Introduction, [1][2][3][4][5][6][7][8][9][10][11] 2. Review and Perspective Articles, [12][13][14][15][16][17][18][19] 3. Methods Papers, [20][21][22][23][24][25][26][27][28][29] 4.…”
Section: Introductionunclassified